Number of manic episodes is associated with elevated DNA oxidation in bipolar I disorder - Soeiro-de-Souza, Márcio Gerhardt; Andreazza, Ana C.; Carvalho, Andre F.; Machado-Vieira, Rodrigo; Young, L. Trevor; Moreno, Ricardo Alberto (The international journal of neuropsychopharmacology, 2013)
Bipolar disorder (BD) is a major public health problem characterized by progressive functional impairment. A number of clinical variables have been associated with progression of the disease, most notably number of affective episodes and presence of psychotic symptoms, both of which correlate with greater cognitive impairment, lower response rates for lithium, and possibly lower levels of neurotrophic factors. Oxidative damage to cytosine and guanosine (8-OHdG) has been described as a modulator of DNA methylation, but the extent of DNA oxidative damage involvement in BD remains unclear. The aim of this study was to evaluate the extent of DNA oxidative damage to 8-OHdG and 5-methylcytosine (5-HMec), as well as global methylation (5-Mec), in BD patients and healthy controls. Potential association with clinical variables was also investigated. DNA levels of 8-OHdG, 5-HMec and 5-Mec were measured in 50 BD type I patients and 50 healthy controls. DNA 8-OHdG levels were higher in BD patients compared to healthy controls and found to be positively influenced by number of previous manic episodes. BD subjects had lower levels of 5-HMec compared to controls, whereas this measure was not influenced by the clinical features of BD. Number of manic episodes was correlated with higher levels of 8-OHdG, but not of 5-Mec or 5-HMec. Lower demethylation activity (5-HMec) but no difference in global 5-Mec levels was observed in BD. This finding suggests that oxidative damage to 8-OHdG might be a potential marker of disease progression, although further prospective cross-sectional studies to confirm neuroprogression in BD are warranted.